Problématique de l’abattage d’arbres dans la chefferie de Bangengele, Province du Maniema, en R D Congo. - MUKULUMANIA MUNGAZI DIDO (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
A tree cutting survey was conducted in the Bangengele Chiefdom, Kailo Territory, Maniema Province, Democratic Republic of Congo, during the period from January 15 to June 15, 2019. The objective of the The purpose of this study was to analyze the consequences of tree felling caused by the Makala phenomenon in the study area and to suggest possible solutions. The survey was carried out among 150 farmers (charcoal and carpenters) living in nine villages (Enombe, Katako, Lubelenge, Odimba, Oleko, Kalemba, Shoko, Bateswayi, Kasuku) belonging to the Bangengele chiefdom in the Kailo territory. chosen randomly. The data were processed and analyzed using Excel 2010 software. The results obtained showed that tree cutting is carried out by men (100%), with a dominant age range of 18 to 50%. years, and 84.7% of these actors have completed high school. The respondents stated that the main reasons for cutting down trees in the Bangengele chieftaincy are the manufacture of charcoal (39.5%), the search for financial means (27.0%), the firing of bricks ( 17.5%), forest loss in the region (9.0%) and furniture manufacturing (7%). With regard to the slaughter sites, the respondents stated that the felled trees are found in forests / forest galleries (43.3%), savannas (34.5%), orchards (18.0%), "village" residential plots (4.0%). The immediate consequences of tree cutting are the scarcity of trees (54.0%) and the disappearance of these forest species (46.0%). To reduce the practice of felling trees in the study area, awareness of the population (33.5%), the formal ban on cutting trees (18.0%), the application of Tree cutting regulations (48.5%) are solutions to be taken into account.